The Neolithic of Europe : Papers in Honour of Alasdair Whittle - Bickle, Penny (Oxbow Books, Limited, 2017)
Front Cover -- Title -- Copyright -- Contents -- List of figures -- List of tables -- List of contributors -- Tabula gratulatoria -- 1. Introduction: Alasdair Whittle and the Neolithic of Europe Joshua Pollard, Penny Bickle, Vicki Cummings and Daniela Hofmann -- 2. 'Very like the Neolithic': the everyday and settlement in the European Neolithic Penny Bickle and Evita Kalogiropoulou -- 3. The end of the tells: the Iron Age 'Neolithic' in the central and northern Aegean James Whitley -- 4. Encounters in the watery realm: early to mid-Holocene geochronologies of Lower Danube human-river interactions Steve Mills, Mark Macklin and Pavel Mirea -- 5. Buried in mud, buried in clay: specially arranged settlement burials from in and around the Danubian Sárköz, Neolithic southern Hungary Eszter Bánffy, János Jakucs, Kitti Köhler, Tibor Marton, Krisztián Oross and Anett Osztás -- 6.The chosen ones: unconventional burials at Polgár-Csőszhalom (north-east Hungary) from the fifth millennium cal BC Pál Raczky and Alexandra Anders -- 7. A tale of two processes of Neolithisation: south-east Europe and Britain/Ireland Rick Schulting and Dušan Borić -- 8. Stag do: ritual implications of antler use in prehistory László Bartosiewicz, Alice M. Choyke and Ffion Reynolds -- 9. Towards an integrated bioarchaeological perspective on the central European Neolithic: understanding the pace and rhythm of social processes through comparative discussion of the western loess belt and Alpine foreland Amy Bogaard, Stefanie Jacomet and Jörg Schibler -- 10. Size matters? Exploring exceptional buildings in the central European early Neolithic Daniela Hofmann and Eva Lenneis -- 11. Feasts and sacrifices: fifth millennium 'pseudo-ditch' causewayed enclosures from the southern Upper Rhine valley Philippe Lefranc, Anthony Denaire and Rose-Marie Arbogast.